The analysis of the determinants of free-size t-shirt for men - Lazatin, Farah Lisa A.
This research aims to establish the definition of the free size to be able to assist the consumers and manufacturers in determining the concept of free size round neck T-shirts sold and manufactured locally. A total of seventy-one (71) branded new T-shirts, regardless of the logo, labeled free size, were measured in tow (2) major department stores in Metro Manila, namely SM City and Robinsons's Galleria. Instruments used to collect data were the actual measurement of he neck width, shoulder length, sleeve length, sleeve opening, chest, center front, center back and the highest point of shoulder, actual weight of fabric, price, consumer survey, manufacturer survey and from the review of related literature. Results of the study showed that there are two (2) ways of sizing T-shirts. The functional way where you use the small, medium, large and extra large as a set by the Philippine National Standard which is based on the consumer population average size. The other way of sizing T-shirts are based on fashion dictated by aesthetics which creates the concept of free size. It is the one accepted by society as fashionable. Therefore, free size t-shirt on an average measurement is between large and extra large based on actual data in relation to the standards set by the Philippine National Standard.